2018
DOI: 10.3390/su10020345
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Decoupling between Rural-to-Urban Migrants and Urban Land Expansion in Hubei Province, China

Abstract: Rapid urbanization in China has caused a large number of rural-to-urban migrants (RUMs) and rapid urban land expansion (ULE). Understanding the relationship between RUMs and ULE has important implications for urban sustainable development. This study explored the spatial patterns of RUMs and ULE in Hubei Province from 2009 to 2014, and analyzed the relationship between the two using a decoupling model. The results show that: (1) a large proportion of the rural population migrated to urban areas in Hubei Provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…where ∆ is the lagged values of the first difference of the variable. Equations (11)- (13) show that the most appropriate form of equation is the Augmented Dickey-Fuller, as shown in Equation (14).…”
Section: Stationary Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…where ∆ is the lagged values of the first difference of the variable. Equations (11)- (13) show that the most appropriate form of equation is the Augmented Dickey-Fuller, as shown in Equation (14).…”
Section: Stationary Featuresmentioning
confidence: 99%
“…The results of the study demonstrate that the changes in value of the economic subsystem are the cause of changes in the ecology and construction land use (CLU) subsystems, while the changes of value of the ecology and CLU subsystems are the root cause of each other. In addition, Liu et al [13] explored the trends between Rural-to-Urban Migrants (RUMs) and Urban Land Expansion (ULE) in Hubei, China from 2009 to 2014 by applying a decoupling model. The study concluded that an irregularly distributed large percentage of the rural population was moving to urban areas, and that urban land use is both rising rapidly and is inefficient.…”
mentioning
confidence: 99%
“…The urbanization rate and built-up area per capita have increased rapidly and are expected to peak in approximately 2020. Specifically, the built-up area per capita in 2014 was 127.02 square meters per person [6,7], showing that with the steady advancement of Chinese urbanization, the previous expansion-type development has proven to be unsustainable, the development mode of incremental planning based on spatial expansion has changed, and urban development planning has gradually shifted from incremental expansion to stock exploration [8][9][10][11]. The development model of inventory planning takes urban renewal as its driver, starting by improving public facilities, optimizing the structure of industrial land, accelerating urban transformation, and upgrading infrastructure [12].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of related studies have focused on carbon storage in temperate and tropical forests in the north, whereas few have investigated the carbon density of subtropical forests [7,10,13,14], particularly forests in Hubei Province. Hubei Province is located in the climate zone that connects the subtropical zone to the warm temperate zone and is one of the regions that is highly sensitive to global climate change [18]. Evergreen coniferous, deciduous broadleaf, and mixed forests are widely distributed in this region [16].…”
Section: Introductionmentioning
confidence: 99%